Sight, Sound, Motion : Applied Media Aesthetics - Zettl, Herbert (Australia : Cengage Learning, 2017)
This book describes the major aesthetic image elements - light and colour, space, time-motion, and sound - and how they are used in television and film. It provides comprehensive coverage of aesthetic theory and inclusion of visuals and examples.
Previous edition: 2014.
Includes bibliographical references and index.
Keywords: Cinematography; Motion pictures -- Production and direction; Motion pictures -- Aesthetics; Television -- Aesthetics; Photography